Unveiling the nexus: The tumor microenvironment as a strategic frontier in viral cancers - Queenie Fernandes (14557388) (2024)
Viral infections are a significant factor in the etiology of various cancers, with the tumor microenvironment (TME) playing a crucial role in disease progression. This review delves into the complex interactions between viruses and the TME, highlighting how these interactions shape the course of viral cancers. We explore the distinct roles of immune cells, including T-cells, B-cells, macrophages, and dendritic cells, within the TME and their influence on cancer progression. The review also examines how viral oncoproteins manipulate the TME to promote immune evasion and tumor survival. Unraveling these mechanisms highlights the emerging paradigm of targeting the TME as a novel approach to cancer treatment. Our analysis provides insights into the dynamic interplay between viruses and the TME, offering a roadmap for innovative treatments that leverage the unique characteristics of viral cancers. Other Information Published in: Cytokine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cyto.2024.156827